A Case Report on Decompensated Cirrhosis of Liver in Pregnancy (Bangladesh Journal of Medicine, 2013)
Pregnancy in women with advanced liver disease is rare. Cirrhosis results in metabolic and hormonal derangements that lead to anovulation and amenorrhea1. In this paper we described the case of a successful pregnancy in a young woman with advanced cirrhosis due to hepatitis B virus infection. DOI: http://dx.doi.org/10.3329/bjmed.v22i2.13591 Bangladesh J Medicine 2011; 22: 60-62